Profile of critical thinking skills of pre-service physics teachers: a preliminary study. Issue 3 (February 2019) - Dholo, T F; Firman, H; Kaniawati, I; Rusdiana, D
Abstract: Critical thinking skills is one of the high-level thinking skills that students must have in this era of technology and information. Critical thinking is needed for students who are preparing to enter a complex working field.This study aims to determine the profile of critical thinking skills of pre-service physics teachers at the University of Flores. The method used is descriptive survey method. The result of the study shows that: 1) The students' critical thinking skills are spread in 5 categories, namely "very high" by 10%, "high" by 22.5%, "medium" by 32.5%, "low" by 10% and "very low" 25%; 2) Students need to be familiarized with questions that stimulate critical thinking skills; 3) A physics-based thinking test tool is needed for critical students of pre-service physics teacher.